(untitled) (Cardiovascular Journal, 2014)
Back ground: Hypertension is one of the most important modifiable risk factors for cardiovascular disease (CVD) and stroke. Dyslipidemia is closely associated with hypertension. Dyslipidemia and hypertension are the commonest risk factors for CVD. The aim of the present study was to compare different lipid parameters among newly diagnosed hypertensive patients with normotensive subjects in Bangladesh and find out the relationship. Methods: This study was a cross sectional study in which 42 newly diagnosed hypertensive patients who were on no antihypertensive medication and 42 subjects with normal blood pressure (normotensive) were enrolled for compare. Lipid parameters total cholesterol (TC), triglyceride (TG), low density lipoprotein ( LDLc) and high density lipoprotein (HDLc) were estimated by Enzymatic colorimetric test. Results: The mean systolic blood pressure of hypertensive and normotensive were 154.6±22.5 vs111.50±3.42 mmof.Hg and mean diastolic blood pressure were 93.2±5.20 vs 71.44± 3.21mm of Hg. The mean of SBP and DBP of hypertensive patients was found to be higher than normotensive (p< 0.05). There was significant increase in different lipid levels namely TC 199.4±44.5 vs188.7±37.9 mg/dl, TG155.9±88.8 vs 121.9±73.2 mg/dl and LDLc 119.8±35.6 vs112.7±28.6 mg/dl in hypertensive patients as compared to normotensive (p<0.05). However there was no significant difference in HDLc level. BMI and waist circumference showed significant association in hypertensive patients (p<0.001). Conclusion: Analytical results of the study revealed that hypertensive patients have been found to have close association with dyslipidemia, BMI and waist circumference. Hypertension and dyslipidemia can be modified either by proper life style changes or medical management or by the combination of the both. This study suggests that hypertensive patients need measurement of blood pressure and lipid profile at regular interval to prevent heart diseases and stroke. DOI: http://dx.doi.org/10.3329/cardio.v6i2.18350 Cardiovasc. j. 2014; 6(2): 112-115